PERBANDINGAN EFEKTIFITAS PENURUNAN KADAR BOD DAN COD PADA LIMBAH CAIR INDUSTRI TAHU MENGGUNAKAN TANAMAN KAYU APU (Pistia stratiotes) DAN TANAMAN ECENG GONDOK (Eichornia crassipes Solms) - Enggrit Ariana Sari; Koerniasari .; Soekiran Al Jauhari (GEMA LINGKUNGAN KESEHATAN, 2016)
Tofu waste is the waste generated in tofu manufacturing process. The Waste is generated in the form of solid and liquid wastes. The liquid waste contains organic material.  When it is disposed in water without processing, it will cause pollution, such as the reduction of oxygen dissolved in the water causing disturbance on organisms living in the water. This is an actual experimental research by using "pretest-posttest with Control Group" design. This research was conducted with 9 repetitions; each took 30 liters divided into three tubs. The data were then analyzed by using the percent decline formula. The results showed that each treatment was effective to reduce BOD and COD with 2 days contact. BOD reduction was 49.11% and 42.87% for COD reduction by using  water hyacinth plant. With apu-apu, the reduction of BOD was 33.76% and COD was 36.26%. Small and medium industries experiencing problems with the quality BOD and COD level are suggested to make a pond filled with the plants to absorb the levels of BOD and COD to improve the quality of the liquid waste before it is discharged in water bodies. Government institutions are expected to continue to monitor industry that produces waste. Therefore, BOD and COD levels remain below the quality standard that has been set.Keywords    : BOD, COD, Apu-Apu, Water Hyacinth, Tofu waste